Is calcium a link between inflammatory bone resorption and heart disease? - Klein, Gordon L (eLife, 2022)
Several epidemiologic studies associate bone-resorbing chronic inflammatory conditions with increased risk of atherosclerotic heart disease. These include post-menopausal osteoporosis, spinal cord injury, rheumatoid arthritis, and osteoarthritis. Additional studies have noted that the use of anti-resorptive agents following hip fracture, during rheumatoid arthritis, and prior to intensive care management have resulted in reduced overall mortality and mortality from cardiovascular disorders. The careful study of burn patients has allowed us to detect that children and adolescents have a mechanism that protects them from the entry of calcium into the circulation following inflammatory bone resorption. That is, they respond to pro-inflammatory cytokines by up-regulating the parathyroid calcium-sensing receptor (CaSR) with consequent development of hypocalcemic hypoparathyroidism and hypercalciuria. As extracellular calcium appears to exacerbate and/or prolong the inflammatory response, this responsiveness of the CaSR to inflammatory cytokines may be the factor that reduces cardiovascular morbidity and mortality. In adults with chronic inflammatory conditions, the ability of the CaSR to respond to pro-inflammatory cytokines is lost, suggesting that the calcium that enters the circulation following inflammatory bone resorption may persist in the circulation, entering the small coronary blood vessels and favoring the formation of coronary artery calcification, inflammation, and consequent cardiovascular disease.
Keywords: cardiovascular disease; chronic inflammation; calcium-sensing receptor; burns; calcium